Introduction: Mimetic Governmentality, Colonialism, and the State - Roque, Ricardo (2018)
Engaging critically with literature on mimesis, colonialism, and the state in anthropology and history, this introduction argues for an approach to mimesis and imitation as constitutive of the state and its forms of rule and governmentality in the context of late European colonialism. It explores how the colonial state attempted to administer, control, and integrate its indigenous subjects through mimetic policies of governance, while examining how indigenous polities adopted imitative practices in order to establish reciprocal ties with, or to resist the presence of, the colonial state. In introducing this special issue, three main themes will be addressed: mimesis as a strategic policy of colonial government, as an object of colonial regulation, and, finally, as a creative indigenous appropriation of external forms of state power.